(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In recent years, digital images have found extensive use across various applications. These applications can encompass social media platforms and crucial applications, such as those used in military and medical contexts. Nevertheless, cyber attacks and privacy issues pose significant security challenges for digital images. Consequently, various methodologies have been suggested to guarantee privacy and security. Cryptography is one of the first fields of study that comes to mind. Science has made great strides in the field of encryption. To keep sensitive information secret, encryption techniques are used. Multiple forms of encryption are used to keep digital photos private and unaltered. In-depth consideration is given to the Elliptic Curve Cryptography (ECC) image encryption method in this paper. This research examines how efficiently and securely images may be sent using ECC. ECC is a public key cryptography using elliptic curve mathematics to increase security. The study will likely look into how ECC can be used effectively in image sharing or distribution processes to ensure that photos are secure from unauthorized access and swiftly transferred. The experimental findings demonstrate that our approach yields superior outcomes concerning various evaluation indicators.